Interpretation of small specimen creep test and recommendations on standardisation of impression creep test method - Dyson, Charles N.C. (2019)
In-service monitoring of power plant components toward later stages of plant life requires several methods for evaluation. Strain monitoring, metallography and ultrasonic techniques are the most common for inspection. Sampling and mechanical testing are novel techniques that can be used alongside the tools mentioned above. Sampled material is mechanically tested using non-standard small specimens, generating creep data for components that operate in the creep range. Non-standard small specimen creep test methods include sub-size uniaxial, small punch, impression, small ring and two bar creep test techniques. The impression creep test is the focus of this thesis, consisting of a square specimen loaded by a flat-ended rectangular indenter, of which the recommended dimensions are 10x10x2.5mm. Conversions to equivalent uniaxial creep strain and stress are obtained through reference stress techniques. ‘Round Robin’ testing between several independent labs using different test rig set-ups has been used to provide feedback for the progression to standardization of the test technique. It is also shown how the test method can be used to determine the creep strength of high temperature components. Furthermore, the test method is used to characterise pre-strained materials at several strain levels to assess the impact on creep strength. Scoop sampling is integral to using the small samples for component risk management. Therefore, the impact of sampling on the component is assessed using creep continuum damage mechanics, a by product of which was the development of two new test specimens along with a novel validation method for the material model. Progress has been made on the standardisation of the impression creep test technique, with recommendations made based on the analysis in this thesis. A procedure for creep strength ranking of components is suggested and component-sampling tolerances are outlined too based on finite element analysis.